2003
DOI: 10.1016/s0095-0696(03)00031-7
|View full text |Cite
|
Sign up to set email alerts
|

Plant vintage, technology, and environmental regulation

Abstract: Does the impact of environmental regulation differ by plant vintage and technology? We answer this question using annual Census Bureau information on 116 pulp and paper mills' vintage, technology, productivity, and pollution abatement operating costs for 1979-1990. We find a significant negative relationship between pollution abatement costs and productivity levels. This is due almost entirely to integrated mills (those incorporating a pulping process), where a one standard deviation increase in abatement cost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
150
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 492 publications
(155 citation statements)
references
References 17 publications
4
150
0
1
Order By: Relevance
“…In addition, although Leeuwen et al (2013) confirmed the "weak" Porter hypothesis, it did not confirm the "strong" Porter hypothesis in their study [10]. Gray et al (2001) pointed out that regulation in the entire manufacturing industry in the United States would lead to a productivity drop of 9.3% [15]. Bezdek M. (2012) added that strict air quality regulations have contributed to a 2.6% decline in the productivity of the American aircraft manufacturing industry [16].…”
Section: Environmental Regulation and Green Technology Innovationmentioning
confidence: 91%
“…In addition, although Leeuwen et al (2013) confirmed the "weak" Porter hypothesis, it did not confirm the "strong" Porter hypothesis in their study [10]. Gray et al (2001) pointed out that regulation in the entire manufacturing industry in the United States would lead to a productivity drop of 9.3% [15]. Bezdek M. (2012) added that strict air quality regulations have contributed to a 2.6% decline in the productivity of the American aircraft manufacturing industry [16].…”
Section: Environmental Regulation and Green Technology Innovationmentioning
confidence: 91%
“…They find that the data are consistent with the weaker version of the Porter hypothesis. 5 Working on a sample of plants in the pulp and paper industry, Gray and Shadbegian (2003) find among others that total pollution abatement costs reduce productivity by an average 4.8% across all the plants.…”
Section: Environmental Regulation and Environmental Performancementioning
confidence: 99%
“…Ă©galement, un nombre croissant de recherches montrent que les consommateurs sont effectivement prĂȘts Ă  payer un peu plus pour des produits qui ont moins d'impacts sur l'environnement (voir par exemple Roe et al, 2001;Bjorner et al, 2004). Par contre, il existe beaucoup plus de recherches qui dĂ©montrent que, contrairement aux attentes de Porter, la RE a un impact nĂ©gatif sur la croissance de la productivitĂ© (par exemple gollop et Robert, 1983;dufour, Lanoie et Patry, 1998;gray et Shadbegian, 2003). L'impact peut ĂȘtre assez important pour les industries fortement polluantes comme par exemple l'industrie de la production d'Ă©lectricitĂ© thermique 12 .…”
unclassified